2016
DOI: 10.1002/pros.23275
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epigenetic Modification and Immunomodulation in a Murine Prostate Cancer Model

Abstract: Decreased expression of CTA by prostate cancer may be a means of escaping immune monitoring. Combination of epigenetic modifications and immunomodulation by 5-AzaC and lenalidomide increased tumor immunogenicity and enhanced DC function and may be used in the treatment of advanced prostate cancer. Prostate 77: 361-373, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Epigenetic drugs might then result in making PCa cells more immunogenic and amenable to targeting by immune therapies. Similar results were obtained by Sulek et al [152], which additionally demonstrated that combining lenalidomide with decitabine induced dendritic cells activity and ability to stimulate T cells. Chemokines that attract effector and regulatory cells to the tumor are very relevant in regulating immune response.…”
Section: Role Of Immunoepigenetics?supporting
confidence: 88%
See 1 more Smart Citation
“…Epigenetic drugs might then result in making PCa cells more immunogenic and amenable to targeting by immune therapies. Similar results were obtained by Sulek et al [152], which additionally demonstrated that combining lenalidomide with decitabine induced dendritic cells activity and ability to stimulate T cells. Chemokines that attract effector and regulatory cells to the tumor are very relevant in regulating immune response.…”
Section: Role Of Immunoepigenetics?supporting
confidence: 88%
“…A summary of most recent studies addressing combination strategies between epigenetics and immune environment in PCa is depicted in Table 3 [108,[141][142][143][144][145][146][147][148][149][150][151][152]. Some studies have focused on epigenetic regulation of response to IFN, where both methylation and acetylation can be involved, as demonstrated by Dunn and collaborators [141].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…Here, a broad range of tumorassociated antigens, such as CEA, MUC1 and PSA, was observed and an association with augmented expression of multiple proteins involved in antigen processing and tumor immune recognition was found (83). Especially in prostate cancer, decreased expression of CTAs has been discovered as a means of escaping immune monitoring, with several studies addressing the role of HDACis and DNMTis (e.g., azacytidine) in increasing tumor immunogenicity (84,85). Although induction of CTAs by azacytidine and trichostatin A was also observed for bladder cancer (86,87), our research did not yield further results regarding immunomodulation through epigenetic therapy in bladder cancer.…”
Section: Epigenetic Immunomodulation In Urological Tumorsmentioning
confidence: 97%
“…Therefore, improving the immunogenicity of cancer is essential to improving cancer immunotherapy. Epigenetic modulators such as azacytidine (Aza) and decitabine (Dec) function as cytosine analogs, which lead to their incorporation into newly synthesized DNA strands during S phase of the cell cycle; these agents have been shown to enhance immunogenicity of tumor cells by inducing the expression of a panel of highly immunogenic cancer testis antigens (CTAs), and result in improved immunotherapy of cancer [51,52]. Both Aza and Dec also induce the expression of tumor suppressor gene p53 [53] and the death receptor Fas [54] on tumor cells.…”
Section: Epigenetic Targeting Of Tumor Cells For Immune Modulationmentioning
confidence: 99%